Corpo e saúde: reflexões sobre o quadro "Medida Certa" - Bezerra, Hudson Pablo de Oliveira (2012)
The present scenario is permeated by different comprehensions about the body and health. These are the result of a historical process experienced by men in different times and social contexts through which were being built. Faced this scenario, we emphasize the media as a powerful means of information and training ideas regarding the body and health of theses. The media also as a means of mediating information we present characteristics of the social scenario where is inserted. In our research we bring reflects about the comprehensions, knowledge and practices propagated by the way the body and health under "Medida Certa" of the program Fantastico the broadcaster Globo Telecommunications, in order to identify how Physical Education, has contributed the construction of knowledge disseminated. Therefore, we focus our analysis to the table "Medida Certa" exhibited by Fantastico in the months of April, May and June of 2011.The data for analysis were collected through the videos shown live in Fantastic and the information provided in the blog that table. Thus, we had 14 videos shown live, 16 videos posted on the blog, 97 posts in blog. As technique of analysis of the datas used of content analysis of the Bardin (2011). About body obtained as analytical categories: body as operating system; biological body; fragmented body exterior to the subject; body trailer quantified to patterns; subject body. How to health we analyze the categories of health existential: health existential based in biological indices of normality; health existential associated with weight loss and aesthetic patterns; health existential associated with physical activity and nutritional control; and finally we propose a comprehension of health existential. Therefore, from the analysis of the data evidenced a predominance of comprehensions, knowledge and practices about the body and health guided the biological constituents of the body, quantification and classification in medium and normal patterns on pervasive forms of care, in the linear association among physical activity and nutritional control with health, evidenced that Physical Education has contributed to these constructions, through some of his discourses with emphasis on biological aspects. Thus, in our study we advocate an understanding of not only the body as object, but also as a subject clipped by organic, cultural, historical and social elements, a living body, feeling, desire and above all expresses itself, and health viewed as something body, interlaced through the biological, cultural, historical and emotional aspects of this body that coexist in this society